Improvement of soft soils using geogrid encased stone columns - Gniel, Joel; Bouazza, Abdelmalek (Geotextiles and geomembranes, 2009)
In recent years, geotextile encasement has been used to extend the use of stone columns to extremely soft soils. Although the technique is now well established, little research has been undertaken on the use of other encasement materials such as geogrid. This paper discusses the results of a series of small-scale model column tests that were undertaken to investigate the behaviour of geogrid encased columns. The tests focused on studying the effect of varying the length of encasement and investigating whether a column that was partially encased with geogrid would behave similarly to a fully-encased column. In addition, isolated column behaviour was compared to group column behaviour. The results of partially encased column tests indicated a steady reduction in vertical strain with increasing encased length for both isolated columns and group columns. Bulging of the column was observed to occur directly beneath the base of the encasement. A significant increase in column stiffness and further reduction in column strain was observed for fully-encased columns, with strain reductions in the order of 80%. This range of performance may lend the techniques of partial and full geogrid encasement to a series of potential site applications.